ANALISIS CUSTOMER REPURCHASE FREMILT HOUSE THAI TEA (Studi Kasus Pada Fremilt House Thai Tea) - Ridwan Sanito; Sudarwati Sudarwati; Ida Aryati (ITB AAS INDONESIA Surakarta, 2020)
This research is expected to be able to prove the effect of product quality, store atmosphere and brand image on repurchasing at FREMILT HOUSE THAI TEA. This study uses quantitative data types by distributing questionnaires to respondents through purposive sampling techniques. By using multiple regression analysis, the results of this study prove that product quality, store atmosphere, and brand image play a role in consumer repurchases. However, store atmosphere is more dominant in this regard. Keywords : product quality, store atmosphere, brand image on repurchasing